2023
DOI: 10.1088/1402-4896/acf62d
|View full text |Cite
|
Sign up to set email alerts
|

Spin wave-assisted enhanced current-driven domain wall movement

Guangjian Gong,
Yu Wang,
Jingguo Hu

Abstract: The track memory based on current driven magnetic domain wall motion is a potential device for the next generation of magnetic information storage. To improve the speed of current driven domain wall motion and reduce the Joule heat, the relevant laws and physical mechanisms of the spin wave assisting current driven domain wall motion in long linear magnetic nanoribbons has been investigated to achieve spin wave assisted enhancement of current driven domain wall motion. The results show that the spin wave assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The [31] shows that the spin wave assistance can enhance the current driven magnetic domain wall movement, so it can be used to reduce driving current. In addition, the previous research has shown that spin wave driving the magnetic domain walls movement depends on its amplitude and frequency [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The [31] shows that the spin wave assistance can enhance the current driven magnetic domain wall movement, so it can be used to reduce driving current. In addition, the previous research has shown that spin wave driving the magnetic domain walls movement depends on its amplitude and frequency [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…To weaken the Joule heating caused by large driving currents [28][29][30], the spin wave assistance can be used to decrease the driving current then reduce Joule heating [31]. Here, we try to use the spin wave assisting to weaken the influence by nanowire bending for current driving magnetic domain wall in U-shaped magnetic nanowires.…”
Section: Introductionmentioning
confidence: 99%